Okužba sečil pri dojenčkih in majhnih otrocih - Kersnik-Levart, Tanja (Medicinski razgledi, 2005)
In this review article, the authors present a survey of urinary tract infections in infants and small children. Relevant terminology is outlined andthe incidence, etiology and diverse clinical pictures of these infections are presented. The importance of accurate diagnosis based on proper urine collection and the need for prompt therapy, especially in the first year of life, are stressed. This is followed by a description of treatment, prognosis and morphologic studies with function tests done after first infection. A modern algorithm of investigations to be performed in children after first urinary tract infection and in those who are healthy or seemingly healthy, butat the highest risk of permanent renal damage, is presented. The content ofthis article was harmonized and approved by the medical board of the Department of Pediatric Nephrology, and represents the current doctrine of this clinical department. In this article, references to urinary tract infection denote bacterial infections of the urinary tract in infants and small children, unless a different population or etiology is specifically stated.
Keywords: Bakterijske infekcije; Urinary Tract Infections; Piurija; Pyuria; Proteinuria; Proteinurija; Radioizotopna renografija; Bacterial Infections; Diagnosis; Sečila, infekcije; Dojenček; Drug Therapy; baby; Otrok predšolski; Radioisotope Renography; Infant; Urografija; Vezikoureteralni refluks; Child, Preschool; sečila; Vesico-Ureteral Reflux; Urography; infekcije; dojenčki